Estimation of age by measuring the Root Length of Mandibular Premolars & Permanent Mandibular Molar - A Digital Radiographic Technique - R Vishwanath; Balaji Rao; Shylesh Lele; G P Mamatha; Shashikanth (Wolters Kluwer Medknow Publications, 2004)
Developing teeth have been considered as a good indicator for determination of age of an individual with unknown birth data. The common methods employed have been radiographic subjective assessment of tooth development and subsequent comparisons with dental charts. The accuracy of these methods has been questioned since the distribution around an estimated age has been more than ±2 years between 10th and 90th percentile. In an attempt to avoid the short coming associated with the subjective methods, a study of objective measurement of root length of mandibular 2nd premolar and permanent 1st molar by intraoral digital radiographic technique was conducted in the age group of 10-14 years and analyzed statistically using stepwise multiple regression models. It is found that the mandibular premolars can be used for age estimation with fair degree of accuracy between the age of 10-14 years.